Global atlas of marine fisheries :a critical appraisal of catches and ecosystem impacts a critical appraisal of catches and ecosystem impacts - Pauly, D. ed (State of the world's oceans series.)
Until now, there has been only one source of data on global fishery catches: information reported to the Food and Agriculture Organization of the United Nations by member countries. An extensive, ten-year study conducted by The Sea Around Us Project of the University of British Columbia shows that this catch data is fundamentally misleading. Many countries underreport the amount of fish caught (some by as much as 500%), while others such as China significantly overreport their catches. The Global Atlas of Marine Fisheries is the first and only book to provide accurate, country-by-country fishery data. This groundbreaking information has been gathered from independent sources by the world's foremost fisheries experts, and edited by Daniel Pauly and Dirk Zeller of the Sea Around Us Project. The Atlas includes one-page reports on 272 nations or regions, plus fourteen topical global chapters. National reports describe the state of the country's fishery, by sector; the policies, politics, and social factors affecting it; and potential solutions. The global chapters address cross-cutting issues, from the economics of fisheries to the impacts of mariculture. Extensive maps and graphics offer attractive and accessible visual representations. While it has long been clear that the world's oceans are in trouble, the lack of reliable data on fishery catches has obscured the scale, and nuances, of the crisis. The Atlas shows that, globally, catches have declined rapidly since the 1980s, signaling an even more critical situation than previously understood.--